Worldwide Sports Injury Prevention - Luciana D Mendonça; Joke Schuermans; Evi Wezenbeek; Erik Witvrouw (International Journal of Sports Physical Therapy)
The number one goal of the sports physical therapist is to make sure that the athlete is in optimal shape to perform, but with a minimal risk for developing an injury at the same time. The aim of this International Federation of Sports Physical Therapy (IFSPT) Perspective is to raise awareness about the importance of contextual and behavioral factors when planning and implementing injury prevention. Also, it outlines the potential role of the IFSPT as a facilitator of data and information exchange among sports physical therapists worldwide.